2013
DOI: 10.1165/rcmb.2012-0476oc
|View full text |Cite
|
Sign up to set email alerts
|

Faslodex Inhibits Estradiol-Induced Extracellular Matrix Dynamics and Lung Metastasis in a Model of Lymphangioleiomyomatosis

Abstract: Lymphangioleiomyomatosis (LAM) is a destructive lung disease primarily affecting women. Genetic studies indicate that LAM cells carry inactivating tuberous sclerosis complex (TSC)-2 mutations, and metastasize to the lung. We previously discovered that estradiol increases the metastasis of TSC2-deficient cells in mice carrying xenograft tumors. Here, we investigate the molecular basis underlying the estradiol-induced lung metastasis of TSC2-deficient cells, and test the efficacy of Faslodex (an estrogen recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…In TSC2-deficient cells, 17-b oestradiol increases cell size, and promotes cell survival, metastasis and lung colonisation via mitogen-activated protein kinase/extracellular signal-regulated kinase kinase (MEK)-dependent pathways [20][21][22][23]. Oestradiol also induces the expression and activity of matrix metalloproteinase-2 in TSC2-deficient cells, which may contribute to lung destruction [20,24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In TSC2-deficient cells, 17-b oestradiol increases cell size, and promotes cell survival, metastasis and lung colonisation via mitogen-activated protein kinase/extracellular signal-regulated kinase kinase (MEK)-dependent pathways [20][21][22][23]. Oestradiol also induces the expression and activity of matrix metalloproteinase-2 in TSC2-deficient cells, which may contribute to lung destruction [20,24].…”
Section: Introductionmentioning
confidence: 99%
“…Oestradiol also induces the expression and activity of matrix metalloproteinase-2 in TSC2-deficient cells, which may contribute to lung destruction [20,24]. The prometastatic effects of oestradiol on TSC2-deficient cells can be blocked, in vitro and in vivo, by the US Food and Drug Administration approved agent fulvestrant (Faslodex; AstraZeneca, London, UK) [20], which leads to degradation of ER-a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these difficulties were shared by previous studies conducted in this and other rare diseases. LAM research is currently very active, with several clinical trials ongoing or in preparation using aromatase inhibitors or the agent fulvestrant (which targets the oestrogen receptor-a [30,48,49]), targeting autophagy [50] or using simvastatin in combination with sirolimus [51,52]. VEGF-D [53], or its receptor VEGFR-3, Rheb [30], integrins, etc., may also represent effective targets for therapy.…”
mentioning
confidence: 99%
“…Little is known about the molecular mechanisms underlying E 2 -induced survival and metastasis of tuberin-deficient cells. The impact of E 2 on the growth of tuberin-deficient cells has been reported (9,(33)(34)(35)(36)(37)(38)(39)(40). Gu et al reported that E 2 activates Erk1/2 and increases the migration and invasion of tuberin-deficient cells (41).…”
Section: Discussionmentioning
confidence: 97%